Examining the UNODC’s Guide to Implementing Family Skills Training Programmes for Drug Abuse Prevention in Terms of Turkey’s Needs - İşmen Gazioğlu, Esra and Canel, Azize Nilgün (Addicta: The Turkish Journal on Addictions, 2018)
This study intends to examine the United Nations Office on Drugs and Crime’s Guide to Implementing Family Skills Training Programmes for Drug Abuse Prevention in the context of Turkey. For this purpose, the first part of the study discusses the family-training applications in Turkey, after which the aforementioned guide is summarized. Lastly, what will be developed for preventing substance dependence in Turkey in the direction of the information in the guide is found in the Guide to Implementing Family Skills Training Programmes for Drug Abuse Prevention, including the structure, content, and functionality of training programs that also cover families. To